Cytotoxic activity, selectivity, and clonogenicity of fruits and resins of Saudi medicinal plants against human liver adenocarcinoma - Ali Hendi Alghamdi; Aimun A. E. Ahmed; Mahadi Bashir; Hiadar Abdalgadir; Asaad Khalid; Mohamed E. Abdallah; Riyad Almaimani; Bassem Refaat; Ashraf N. Abdalla (Drug Target Insights, 2024)
Background: Edible fruits and resins provide various benefits to mankind including potential medicinal applications. This study aimed to determine the cytotoxicity, selectivity, and clonogenicity of fruits and exudates of certain Saudi medicinal plants (Anethum graveolens (BEP-09), Opuntia ficus-indica (L.) Miller (BEP-10), Boswellia serrata Roxb. ex Colebr. (BEP-11), and Commiphora myrrha (BEP-12)) against human liver adenocarcinoma (HepG2).